Risk factors for recurrence in colorectal cancer: a retrospective analysis in a regional Australian hospital. Issue 11 (30th September 2021) - Holt, Jonathon; Schwalb, Heinrich; Elbourne, Hugh; te Marvelde, Luc; Reid, Caitlin
Abstract: Background: Colorectal cancer is the third most commonly diagnosed malignancy in Australia. Up to a third of patients who have undergone surgery with curative intent for colorectal cancer will have a recurrence of disease leading to significant morbidity and mortality. Regional Australians have disproportionately worse outcomes. Aim: To identify factors associated with recurrence in colorectal cancer patients treated at a regional Australian hospital. Methods: This study is a retrospective cohort analysis. Consecutive patients who have undergone curative resection at a regional public and private hospital by three surgeons from a single surgical practice for either rectal cancer or colon cancer were included. Prognostic indicators of recurrence were examined via both univariate and multivariate time‐to‐event analyses. Results: Three hundred nine patients were included with 43 recurrences. Thirty presented with distant metastases, seven presented with locoregional recurrence and six presented with locoregional as well as distant recurrence. In univariable analysis, higher rates of recurrence were associated with tumour type, higher AJCC summary stage, higher preoperative levels of CA19‐9, perineural invasion, lymphovascular invasion, <12 nodes examined, positive lymph nodes and emergency surgery status. On multivariable analysis recurrence remained associated with tumours with a mucinous and/or signet cell component, positive nodes and <12 lymph nodes examined. Conclusion: A combination of patient and treatment factors are relevant in determining the risk of recurrence for stage I–III colorectal cancer. This study emphasises the importance of histology in determining risk, particularly the number of nodes examined. CEA 19–9 may also be a useful pre‐operative predictor of recurrence. Abstract : Risk factors for recurrence ‐ univariate analysis.